Fluorescent iridium(iii) coumarin-salicylaldehyde Schiff base compounds as lysosome-targeted antitumor agents. Issue 18 (21st April 2020) - Liu, Cong; Liu, Xicheng; Ge, Xingxing; Wang, Qinghui; Zhang, Lei; Shang, Wenjing; Zhang, Yue; Yuan, Xiang Ai; Tian, Laijin; Liu, Zhe; You, Jinmao
Abstract : Fluorescent iridium(iii ) coumarin-salicylaldehyde Schiff base antitumor compounds change the ROS and Δ Ψ m, induce lysosomal damage, and lead to apoptosis. Abstract : Six fluorescent half-sandwich iridium(iii ) coumarin-salicylaldehyde Schiff base (O^N) compounds ([( η 5 -Cp*)Ir(O^N)Cl]) were prepared and characterized. The introduction of a coumarin unit increased the antitumor activity (IC50 : 9.9 ± 0.1 μM–40.7 ± 12.9 μM) of these compounds, the best of which was nearly two times that of clinical cisplatin. The results of laser confocal microscopy demonstrated that these compounds possessed an energy-dependent cellular uptake mechanism, accumulated in the lysosomes (Pearson co-localization coefficient: ∼0.7), damaged the integrity of the lysosomes, and induced apoptosis. The compounds could also decrease the mitochondrial membrane potential, catalyze the oxidation of the coenzyme (nicotinamide-adenine dinucleotide) and improve the levels of the intracellular reactive oxygen species, following an antitumor mechanism of oxidation. Additionally, these compounds could block the metastasis of tumor cells. Above all, these iridium(iii ) compounds show potential as antitumor agents with dual functions: lysosomal damage and anti-metastasis.